Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Denote by tridiag($a$,$b$,$c$) the tridiagonal matrix of size $n \times n$ with diagonal elements $b = (b_1, \ldots,b_n)$. Let $a = (a_1, \ldots, a_{n-1})$ and $c = (c_1,\ldots,c_{n-1})$ be the entries of the other two diagonals.

I am trying to compute $$\text{tridiag}(a,b,c)^{\intercal}\text{tridiag}(c,b,a)$$ where $a = (-1, \ldots, -1)$, a vector of $(n-1)$ ones, $b = (1,\ldots,1)$ and $c = (c_1,c_2,\ldots,c_{i-1},c_n)$ is given by $c_1 = -1-\theta$, $c_2 = c_3 = \ldots = c_{n-1} = -\theta k$ and $c_n = 1-\theta$. Here, $\theta$ and $k$ are real numbers.

I found a few articles that gave inverses of specific tridiagonal matrices, but none of this form. Any help would be greatly appreciated.

[edit] To clarify, I'm trying to calculate

$$\left(\begin{array}{cccc} (-1-\theta) && 1 && \ldots \\ -1 && -\theta k && 1 &&\ldots\\ \vdots&&-1&&-\theta k && 1 &&\ldots\\ \vdots && && \ddots &&\ddots && \\ \cdots && && &&\cdots && 1 \\ \cdots && && && -1 && 1-\theta \end{array}\right)^T \left(\begin{array}{cccc} (-1-\theta) && 1 && \ldots \\ -1 && -\theta k && 1 &&\ldots\\ \vdots&&-1&&-\theta k && 1 &&\ldots\\ \vdots && && \ddots &&\ddots && \\ \cdots && && &&\cdots && 1 \\ \cdots && && && -1 && 1-\theta \end{array}\right)$$

where all the dots denote zeroes. Apologies for the broken lay-out, I don't know how to fix this.

share|cite|improve this question
up vote 1 down vote accepted

I assume that $A^T$ denotes the transpose of $A$. There is a mistake. The considered product matrix (in EDIT) is not $tridiag(a,b,c)^T tridiag(c,b,a)$ but $tridiag(a,b,c)^T triadiag(a,b,c)$.

  1. In the edit case, the result $U$ is the symmetric matrix ($\theta$ is denoted by $t$)

    $u_{1,1}=t^2+2t+2,u_{n,n}=t^2-2t+2$, the other $u_{i,i}=k^2t^2+2$, $u_{1,2}=u_{2,1}=kt-t-1,u_{i,i+2}=u_{i+2,i}=-1,u_{n-1,n}=u_{n,n-1}=-kt+t-1$, the other $u_{i,j}$ being zero.

    1. Now $tridiag(a,b,c)^T tridiag(c,b,a)=tridiag(c,b,a)^2$. Is that you want ?
share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.